Islamic Business Ethics and Islamic Microfinance in Pesantren Gontor - Nugraha, Ahmad Lukman (Shirkah: Journal of Economics and Business, 2017)
Islam affirms that there stand for mutual affect in business processes, until the business practice as a work field recommended to the adherents; while discussing ethics of business activity poped out to minimize cheating and fraud activities. However, Islamic business ethics felt difficult to apply in practice, especially in the business of buying and selling. Modern Islamic Boarding School “Darussalam” Gontor is one of the self-financing and self-help islamic boarding schools in the economic supported by cooperatives in pesantren (koppontren). This paper aims to comprehensively understand the application of Islamic business ethics and focus on the entrepreneurs in business sectors Gontor La-Tansa’s cooperatives. This research had systematically employed mix method research with sequential explanatory design and case study. Gathering data through using questionnaires, interviews, observation and documentation has been performing analysis through data reduction, data display, and data verification. This paper argues that Gontor La-Tansa’s cooperatives sector can run the business activities with implementing business ethics according to the Qur’an and Sunna values. Appear from the height comprehension of the business to the axiom business ethics and the height application in business activities in each business sector. In addition, the role of kiai and business unit supervisor is high. Data displays a level of the height direction (80 percent) and control on the application of business ethics (72 percent). The Islamic business ethics can be applied on firm’s and government’s law with height comprehension and controlling.Keyword: Islamic business ethics, Gontor, pesantren, kiai